Application of (multi-)omics approaches for advancing food allergy: an updated review. (August 2022) - Zhang, Qiaozhi; Wang, Yanbo; Fu, Linglin
Abstract : Food allergy (FA) has become a significant food safety and public health issue, with evidence of increasing prevalence worldwide. Considering the complexity and multifactorial nature of FA, the use of high-throughput technologies, collectively called omics, would benefit the in-depth understanding of the disease etiology and clinical management. This short review provides updates of the application of omics, especially advanced and multi-omics approaches in the research of FA, including exploration of the susceptible factors, distinct adaptive immune responses, biomarkers and metabolic changes, and the role of microbiome dysbiosis. The use of (multi-)omics to identify potential therapeutic targets of FA was also discussed. With the burgeoning advances of omics sciences, a detailed and systematic framework illustrating the biological landscape of the disease is to be allowed. To develop efficacious preventive, diagnostic, and therapeutic tools of FA in the future, the integration of multi-omics data into comprehensive models is highly deserved. Graphical Abstract: ga1 Highlights: Updates of the use of (multi-)omics sciences in food allergy were provided. A specific emphasis was put on the studies using advanced and multiomics. The need and challenges of multi-omics data integration were discussed.